ANALISIS VEGETASI DI KAWASAN HUTAN NAGARI SIMPANG KAPUAK KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA SUMATERA BARAT - Atikah R; Irma Leilani Eka Putri; Reki Kardiman; Filza Yulina Ade (Universitas Cokroaminoto Palopo, 2026)
The Simpang Kapuak Village Forest, located in Mungka Subdistrict, Lima Puluh Kota Regency, is a forest area that plays a role in maintaining environmental balance and supporting the livelihoods of the surrounding communities. This area possesses a high level of biodiversity, making the structure of its forest community a valuable starting point for long-term management and conservation. Therefore, it is important to understand the structure and composition of the vegetation in the Simpang Kapuak Village Forest, Mungka Subdistrict, Lima Puluh Kota Regency. This study is a quantitative descriptive study. The was conducted in the Simpang Kapuak Village Forest, Mungka Subdistrict, Lima Puluh Kota Regency. Data collection was carried out using the single-plot method across 5 plots. Each plot consists of 4 subplots corresponding to the stand size, namely 2 x 2 m (seedlings), 5 x 5 m (saplings), 10 x 10 m (mature trees), and 20 x 20 m (large trees). The research data were analyzed to determine the Importance Value Index (IVI) of the species. The results of the study indicate that there are 27 species belonging to 16 families. The highest Importance Value Index (IVI) was recorded for Syzygium chloranthum at the tree level (134.25%), followed by Litsea grandis at the pole level (144.92%), Syzygium chloranthum at the sapling level (82.97%), and Synedrella nodiflora at the seedling level (32.02%).